The Influence of Environment on Students' Character - Julianta, Ifan; Norlela, Norlela; Sakti, Bintang Celvino; Fernando, Rio (Jurnal Ilmiah Mandala Education (JIME), 2025)
This research aims to analyze the influence of the environment on student character formation. The approach used is a quantitative method with an instrument in the form of a questionnaire which includes an assessment of the family, school and community environment. The research results showed that all indicators in the questionnaire were valid and reliable, with Cronbach's Alpha values above 0.90. The regression model shows a very strong relationship between the independent variables (family and school environment) and the dependent variable (student character), with an R of 0.976 and an R Square of 0.952. These findings confirm that the environment has a significant role in shaping students' character, so that interventions in the family, school and community environments are very important to support the development of students' positive character.